(untitled) (IJOVTECH, 2026)
The capacity of a person to overcome challenges and progress toward their goals is directly related to their level of well-being, which is an essential component of human health. "Well-being" refers to an umbrella concept encompassing multiple dimensions, including "social well-being." The present study aimed to investigate social well-being variation among undergraduates in Ebonyi State based on social support. The study recruited three hundred and twenty-seven undergraduates enrolled in four public tertiary institutions in Ebonyi State, Nigeria. The male and female students were randomly pooled from different departments in the selected institutions. The respondents completed a self-report measure of the Social Well-being Scale, the Multidimensional Scale of Perceived Social Support (MSPSS). A simple linear regression model was deployed to test the study's formulated hypothesis. The result showed that social support statistically significantly predicted the social well-being of undergraduates. The study concludes that social support is essential to an undergraduate's social well-being.